Pengaruh Risiko Kredit dan Risiko Operasional terhadap Profitabilitas pada Perusahaan Bank Tabungan Negara Periode 2016-2020 - Purwanti, Tanti; Manda, Gusganda Suria (Jurnal Maksipreneur, 2024)
This study aims to determine the impact either at the same time or somewhat between credit risk (NPL) and operational hazard (BOPO) on profitability (ROA) in the State Savings Bank listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this research is one banking company. The research method used is a saturated sampling technique. The logical strategy used is various direct relapse examinations using the SPSS program. The results of this study are that simultaneously credit risk (NPL) and operational risk (BOPO) have a large and significant result on productivity (ROA) at the State Savings Bank for the 2016-2020. Partially, the research results on the credit risk variable (NPL) do not have a critical impact and have a negative relationship to profitability (ROA) at the State Savings Bank for 2016-2020 period. Partially, the results of testing the operational risk variable (NPL) have no major impact and have a negative relationship to Profitability (ROA) at the State Savings Bank for the 2016-2020.